Animais como indicadores: Uma ferramenta para acessar a integridade biologica apos a exploraçao madeireira em florestas tropicais? - Azevedo-Ramos, C.; Carvalho, O. de; Nasi, Robert (Instituto de Pesquisa Ambiental da Amazonia (IPAM), 2005)
A literature survey was conducted to assess animal responses to logging and evaluate the usefulness of bioindicators as tools to assess biodiversity conservation in logged tropical forests. The survey indicated that studies on the impact of logging on arthropods and herpetofauna are under-represented. Mammals are the main subject of studies addressing the effect of logging on fauna. Overall, logging does have an effect on some animals but the responses varied between and within animal groups. Additionally, most of the studies conducted so far vary greatly in the forest structures, taxa, methodologies, and logging intensities and histories of the study site, resulting in a lack of comparability among papers. Few studies have investigated linkages between changes in the composition of animal groups and the functional significance of these changes, nor have they correlated responses with environmental changes after logging, complicating determination of cause-effect relationships. Further difficulties were taxonomical complexity, the small number of trained people, the costs of monitoring population trends, the lack of information on the relations between changes in different groups, and the lack of congruence between traditional scales of research (plots) and appropriate scales of land management. The sum of these difficulties suggests that until now animal indicators for monitoring biodiversity conservation in logging operations may be ineffective to implement in forest managements. In this context, indicator development continues to be a critical research need in forest ecology. However, it is good to keep in mind that in management systems, where changes are usually inevitable and most of time desirable, proposed indicators would actually be doing their role of early warning when facilitating the assessment of the acceptable degree of habitat modification. Until there, more broadly inventories are still needed to assess biodiversity status in logging operations.